An unusual new ropy-stemmed species of Burmeistera from the Western Cordillera of the Colombian Andes - Ashokan, Ajith; Muchhala, Nathan; Zuluaga, Alejandro (Phytotaxa, 2025)
Burmeistera (Lobelioideae: Campanulaceae) is the third-largest genus within the centropogonid clade, primarily adapted for bat pollination. The genus is exceptionally rich in the Western Cordillera of the Andes, where recent botanical explorations resulted in the descriptions of several new species. Here, we describe a new species of Burmeistera from the Pacific region of Colombia within the Western Cordillera of the Northern Andes that is characterized by unusually long, hanging, rope-like shoots and inflated fruits.